Modeling of 3D Aquifer Layers using Poisson’s Ratio Analysis HVSR Method in Tembelang Village, Candimulyo District, Magelang Regency - Achmad Syaifuddin Zuhri; Udi Harmoko; Gatot Yuliyanto (Diponegoro University Semarang Indonesia, 2020)
Water is one of vital needs for human beings. People use water to drink, bath, irrigate, and etc. Water supply has become a severe problem over the two past years especially in Tembelang Village, Candimulyo District, Magelang Regency. The research aims to determine the aquifer layers. The method used in this research is seismic method with HVSR (Horizontal to Vertical Spectral Ratio) microtremor survey with 71 measurement points. The HVSR microtremor data is processed to determine Poisson’s ratio from Vp⁄Vs ratio. The obtained Vp⁄Vs ratio from 71 measurement points ranges from 1.63 to 2.64 and Poisson's ratio ranges from 0.20 to 0.42. The Vp⁄Vs ratio parameter to determine an aquifer is more than 1.73 and the Poisson's ratio is more than 0.25. There are 4 zones which are considered to have aquifers, namely at line 1 near point P22 depth of over 184 meters, line 2 near point P8 depth of 108-180 meters, line 3 near point P2 and P3 depth of 91-161 meters, line 4 near point P16, P17, and P18 depth of 32-187 meters. line 5 near point T22 depth of 63-157 meters, point T31 depth of 122-152 meters, and point T40 depth of 71-178 meters. The Vp⁄Vs ratio and Poisson’s ratio are then modeled by using Rockwork 15 to obtain 3D models of acquifers based on the Vp⁄Vs ratio and Poisson’s ratio.